Pengaruh Pemanfaatan Media Pembelajaran Berbasis Teknologi terhadap Hasil Belajar Siswa di SMKN 4 Medan - Marcelinus Tuadon Sirait; Samelino Aritonang; Layninsius Trosky Syukran B. Manalu (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The development of information technology has had a major impact on the world of education, especially for prospective teachers and students interacting in the teaching and learning process. However, in many educational units, the utilization of educational learning technology is not fully optimal. This study serves to analyze the effect of technology-based learning media utilization on student learning outcomes at SMKN 4 Medan. This research uses a descriptive qualitative approach with data collection methods through interviews with the principal, one teacher, and three students. The interview instrument consisted of ten questions designed to explore the use, constraints, and impact of technology in the learning process. The results show that the school has provided technological facilities and encouraged teachers to utilize them, although not all teachers are able to integrate technological media to the fullest. Teachers acknowledge that digital media helps solve educational problems that occur at SMKN 4 Medan. From the students' side, technology-based learning is interesting and helps understanding, but there are still obstacles in the availability of devices and distraction of learning focus.